MORPHEMIC FEATURES IN THE SELECTED POEMS OF CHARLOTTE BRONTË - Syafrida, Nazwa; Melani, Devi; Putri, Andini; Pratama, Aldi Rohim; Nurmala, Dewi (Fakultas Sastra UMN AL Washliyah, 2026)
This study analyzes the morphemic features found in five selected poems by Charlotte Brontë, namely Life, Stanzas, Parting, On the Death of Anne Brontë, and Regret. The study aims to determine how Brontë’s morphological structures contribute to meaning, rhythm, and stylistic character in her poetry. The analysis focuses on identifying free morphemes, bound morphemes, inflectional affixes, derivational affixes, and other word-formation processes. This research employs a qualitative descriptive method using textual documentation and morphemic analysis. The findings, based on an analysis of 1229 total morphemes across the five poems, reveal that all poems are dominated by emotional free morphemes and inflectional bound morphemes (-ing, -ed, -s). Thus, it is concluded that morphological structures play a significant role in shaping the aesthetic effect in Brontë’s poetic works, specifically by combining simple structural forms with expressive word formation.